2015
DOI: 10.1093/jjco/hyv091
|View full text |Cite
|
Sign up to set email alerts
|

Prospective mapping of lymph node metastasis in Japanese patients undergoing radical cystectomy for bladder cancer: characteristics of micrometastasis

Abstract: Objective: To investigate node-disease prevalence including micrometastases and its survival impact on bladder cancer patients. Methods: A total of 60 patients participated in this study, in which extended lymph node dissection was carried out according to the prospective rule (below aortic bifurcation). Radical cystectomy and extended lymph node dissection were performed by open surgery (n = 23) or laparoscopically (n = 37). Perioperative, pathological and follow-up data were collected. Micrometastasis in lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This issue has also been discussed for other neoplasia. Although in some studies, micrometastases were detected in 1%-3% of LN when the remaining fat tissue was embedded after palpation [12,13], these findings have a low prognostic impact [14]. Moreover, even if more LN are found when a complete embedding of the remaining tissue is performed, most of them are negative or were already positive at palpation [15][16][17].…”
Section: Discussionmentioning
confidence: 97%
“…This issue has also been discussed for other neoplasia. Although in some studies, micrometastases were detected in 1%-3% of LN when the remaining fat tissue was embedded after palpation [12,13], these findings have a low prognostic impact [14]. Moreover, even if more LN are found when a complete embedding of the remaining tissue is performed, most of them are negative or were already positive at palpation [15][16][17].…”
Section: Discussionmentioning
confidence: 97%
“…Unfortunately, the failure of several preoperative examinations in detecting micro-metastases is the main reason for the early recurrence of BUC after surgery. The occurrence of micro-metastases is closely related to the clinicopathological characteristics of the tumor (including pathological stage and pathological grade); the more advanced the pathological stage and higher the pathological grade, the more likely is the micro-metastases and recurrence after surgery 28 . In this study, we found that high NUSAP1 expression was significantly correlated with tumor pathological stage, lymph node metastasis, and pathological grade; NUSAP1 expression was significantly higher in patients with T3-T4 TNM stage, higher pathological grades, and positive lymph nodes ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Removal of lymph nodes with micrometastatic deposit may improve survival by reducing overall tumour burden and allowing the immune system and chemotherapeutics to target a smaller number of cancer cells [ 24 ]. New techniques employing immunohistochemical analysis and reverse transcription real-time polymerase chain reaction can aid in detection of micrometastases [ 25 26 ]. It has been demonstrated that patients with micrometastases who are otherwise node-negative on routine analysis have a trend toward worse cancer specific survival and recurrence free survival than truly node-negative patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%